The Impact of Nostalgia Proneness on Online Donation Willingness: The Mediating Effect of Consumer-Brand Relationship - Zhang, Yi; Tao, Wenxia (Frontiers in Psychology, 2022)
COVID-19's wreak havoc broke the quiet life, and the labor market and human livelihoods were strongly negatively affected. The emergence of groups unable to withstand various pressures has increased the appeal of donation behavior to a certain extent. Therefore, under the impetus of COVID-19 and digital background, online donation represented by water drop financing has become popular. In the common difficult period, how to improve the individual's willingness to donate online has become an urgent problem to be solved. To solve this problem, the following studies are carried out: based on a literature review for donation behavior, nostalgia and the consumer-brand relationships, proposing a ‘nostalgia - the relationship variables - donation’ theoretical model, developing some research hypotheses and measurement scales for each variable of theoretical model, carrying out a pre-project research and a large sample survey, confirmatory factor analysis and structural equation modeling analysis. Through above analysis, the paper reached the following conclusions: the main influence factors of personal nostalgic proneness are: insecurity, past experience, loneliness, recovery from grief and so on. There is a positive causal link between nostalgia proneness and familial utility intensity and emotional utility intensity. The greater the degree of the nostalgia intensity of the donor is, the more he trusts in charitable organizations. The donors’ relationship commitment to the charitable organizations significantly influences their online donation willingness. The main source of relationship commitment consists of emotional intensity, followed by trust, and finally familial intensity.